Fashion orientation, shopping mall environment, and patronage intentions: A study of female fashion shoppers. Issue 1 (9th March 2015) - Michon, Richard; Chebat, Jean-Charles; Yu, Hong; Lemarié, Linda
Abstract : Purpose: – The purpose of this paper is to explore female fashion shoppers' perception and response to the mall environment. Specific objectives include a conceptual model of female fashion shoppers' experience in a mall environment incorporating fashion orientation, store personality, shopping mall perception, shopping value, and patronage intentions. Design/methodology/approach: – Empirical testing is done with a latent path structural equation model. Data collection was carried out in a firmly controlled mall intercept survey which produced 312 usable questionnaires. Findings: – Results show that shoppers' fashion orientation hypothesized to be a personality trait is not an antecedent to the perception of the mall environment. Instead, fashion orientation moderates the perception of product and service quality, hedonic shoppers' response, and patronage intentions. The perceived mall personality has a focussed impact on the perception of product and service quality. The mall's sophistication image influences the perception of product quality. On the other hand, the mall's enthusiasm image atmosphere affects the perception of service quality. Perceptions of product and service quality are correlated and trigger positive hedonic and utilitarian shopping benefits. Research limitations/implications: – Because findings from this study cannot be generalized to other situations, the research should be replicated to a variety of mall formats and shopper segments. Furthermore, other fashion-orientation factors (fashion leadership, fashion interest, and anti-fashion attitude) should be considered. However, along with model complexities, increased sample sizes are also required. Future studies may also include male shoppers to investigate differences in fashion motivation and mall shopping experience. Practical implications: – It is concluded that the person-place congruency theory is confirmed and that the shoppers' fashion orientation should be included in the set of segmentation variables. Shopping malls cannot be everything to everyone without risking diluting their image. Downtown urban malls have the opportunity to adopt a well-defined positioning in order to differentiate themselves. Large suburban malls should partition themselves to remove image ambiguities. Mall managers must primarily work on the "meaning" of the mall atmosphere rather "mood." Fashion shoppers are task oriented. Mall managers should design malls to facilitate the shopping experience with highly functional designs, simple layout, and clear signage in support of wayfinding. Originality/value: – Although fashion consumers have been studied from diverse perspectives, there is limited research on the experience of fashion shoppers in a mall setting. This study partly fills this gap in the literature by investigating how female fashion shoppers respond to the shopping center environment and commit to mall patronage.